Implementation of Islamic Counseling Counseling in The Case of Violence Against Women in Households in Sambirejo Village, Gabus District, Pati District - Fita Uljanah; Primi Rohimi (Konseling Religi: Jurnal Bimbingan Konseling Islam, 2021)
his study ains to find out the cause of domestic violence and Islamic counselling service techniques from modin villages. This research uses field research with a qualitative approach. The primary sources are documentation and divorce data. Data collection techniques through interviews or interviews, observation and documentation. Furthermore, the data obtained were analyzed using the data reducation method and data display which summarizes the main things which are then described briefly in descriptive form. The results showed that violence against women (wives) that occurred in the family environment could not be separated from the existence of gender inequality which is one of domestic violence is the village modin. Islamic counselling guidance services for victims of domestic violence provided by the village modin caused a change in attitude from being quiet, aloof, embarrassed to neighbors and friends, with the provision of Islamic counselling guidance the victim became better and easier to sommunicate back to his neighbors and friends.